Rancang Bangun Sistem Pengontrolan Proses Fermentasi Bawang Putih Menjadi Black Garlic Berbasis Web - Hanina Regitha Afifah (Jurnal Jaringan Telekomunikasi, 2020)
Garlic is a very profitable plant, both used as a spice in cooking and medicine. Garlic can also be processed by fermentation and produce black garlic. The garlic fermentation process requires temperature and humidity, both parameters must be monitored and controlled stably. Corresponding With that, a black garlic fermentation tool can be designed by utilizing the NRF node as a communication medium between the fermentation tool and user. In this tool, system control is carried out by Arduino Uno microcontroller which has an input in the form of a DHT21 sensor, this sensor will detect the temperature and humidity in the fermentation tool. The fermentation process takes 2-4 weeks, so this requires timing using RTC. From the results of the temperature, humidity and time information using the communication node between the fermentation tool and monitoring room will be displayed on LCD. In the monitoring room there is a microcontroller which is equipped with a GSM module to send temperature and humidity conditions in the oven to the web every day. The design of fermentation device is 2 electric ovens. On the inside of the oven there is a DHT21 sensor to detect temperature and humidity, and there is a fan that is useful for maintaining the oven temperature conditions to remain stable. In black garlic fermentation using a temperature of 40-50 ° C, time for 21 weeks and a total weight of 3.24 kg in each oven to get the desired maturity of black garlic fermentation.